Reabilitação da área central de São Paulo: 3 projetos de intervenção - Fregonezi, Bruna Beatriz Nascimento (2015)
The dissertation deals with the recent rehabilitation programs in the central region of São Paulo, its distinct proposals, management models and forms of intervention. Through a historic analysis and periodization, three proposals for the redevelopment of the central region were approached: Operação Urbana Centro (1997), Ação Centro (2002) and Nova Luz (2005). Each program presents different postures, perimeter and, mostly, distinct steps drawn to reach the goal of rehabilitation. They were based on preexisting initiatives, based on distinct funding schemes and proposed various processes of social inclusion. The research analyses each program on its own, its visions, reaching an understanding of how they complemented and counterpointed each other, summarizing the transformation by which the center has passed, aiming to contribute to the reformulation of Brazilian urban policies for central areas.